Post-conflict News and Information Needs of West African Farmers: Voices from Côte d’Ivoire and Mali - Assoumane A. Maiga; M. Craig Edwards; Marshall A. Baker; D. Dwayne Cartmell II; Joel M. Jenswold (Journal of International Agricultural and Extension Education, 2016)
During the decades following the independence of Sub-Saharan African countries, many. Farmers were severely affected by armed conflicts. News and information providers could provide important support toward the economic recovery of these farmers and the rebuilding of their communities. This qualitative study sought to explore farmers’ perceptions on the role of media and other sources in disseminating news and information after armed conflicts ceased in Côte d’Ivoire and in Mali. The study involved10 key informants, five from each country. Rigorous qualitative research procedures were used to collect and analyze the study’s data. Six themes emerged from the interviews. Farmers perceived the media were interested in reporting about their regions only during the conflicts. They also indicated the absence of Extension or other forms of rural advisory services during and after armed conflicts. However, all 10keyinformants perceived the media could assist in recovery and rebuilding efforts and should deliver related information in their local languages as well as provide programs targeting women and youth. Recommendations for policy and practice are offered. In addition, topics are identified on which to train communicators and Extension/advisory agents to meet the information needs of farmers who experience the effects of armed conflict
Keywords: Côte d’Ivoire; farmers; information; Mali; media; news; post-conflict